Performance analysis of gravity chemical blockers in the treatment of rising damp in masonry walls - Hoffmann Malaquias, Ronei; Bruschi, Giovani Jordi; de Senna Brisotto, Daiane (Revista ALCONPAT, 2022)
The objective of this work is the performance analysis of the rising damp treatment in walls, through the use of chemical blockers (i.e., crystallizing and water repellant) available in the Brazilian market, with their introduction by gravity. As there are no standardized tests for such a study, experiments conducted by other researchers were used as a reference. The evaluation of the rising damp was achieved by the calculation of the water absorption rate in the specimens, allied with the images obtained by the thermographic camera. From the results, it was concluded that the treatment did not completely reduce the pathological manifestation in the walls, but both products performed well and managed to reduce the water absorption rate considerably.